Check In : The search for meaning and purpose in business - Eynikel, Jochanan, ....- (Tielt : Lannoo Campus, 2021)
One out of every three employees regards his or her job as being completely pointless. Yet all of us - employers, employees and consumers - yearn for purpose in our lives. Our economy is searching for meaning. The key question is how companies can play a role in this. Check-In shows how a meaningful economy is not achieved through fine words and expensive mission statements, but through personal experience. Meaningful work requires a personal check-in on the what, who and why of organisations.
Keywords: Business; betekenis